AB0993 Depressive Symptoms in Patients Consulting for The First Time A Rheumatology Service. (15th July 2016) - Troitiño, C.J.; Adrover, M.; Calizaya, G.; Lares, J.; Durigan, V.; Sandoval, V.; Marcaida, P.; Scarafia, S.; Duarte, V.; Secco, A.; Mamani, M.
Abstract : Background: Depression can easily go unnoticed in routine clinical care. The delay in the diagnosis may increase the risk of chronicity, the number of visits, health care costs and deteriorates the quality of life. 1–3 Objectives: Estimate the prevalence of depressive symptoms in patients consulting for the first time and determine if patients with depression had different reasons for consultation and highest score in the visual analog scale (VAS) of pain than patients without depression. Methods: A observational, prospective study was performed. We included patients who consulted for the first time in Rheumatology Service, excluding these with psychiatric treatments and rheumatic diseases. The PHQ-9 (Patient Health Questionnaire) evaluated the presence of depressive symptoms in the last two weeks. According to the score, they were classified in 4 categories: (1) major depressive syndrome, (2) other depressive disorders, (3) positive depressive symptoms and (4) negative depressive symptoms. To perform the analysis the patients were divided into those with a depressive disorder (1 and 2) and those who did not have it (3 and 4). T-test or Mann Whitney test was used as sample size distribution for continuous variables. Chi square or Fisher exact test was used as expected frequency distribution table for categorical variables. Multivariate logistic regression analysis taking depression as the dependent variable was performed. Results: 121 patients were included in the study. 86% were women, mean age of 49±15 years. The most frequent reasons for consultations were polyarthralgia (35.5%) and back pain (13%). According PHQ-9, 37% of patients were classified in major depressive syndrome and 19% in other depressive disorders. No statistically significant differences between patients with and without a depressive disorder in terms of different reasons were found. However, patients with depressive disorders were more VAS pain (7, IQR 5–8) than patients without depression (5, IQR 4–6) and more days with pain in the week (7, IQR 5–7 vs 5, IQR 3–7), both with p<0.01. Increased frequency of self-medication (61% vs 39%) and sleep disorders (63% vs 37%) among patients with depressive disorders was observed, although these differences were not statistically significant. In the multivariate analysis, the only variable that was found associated with depression was independently VAS pain (OR 1.33, CI 1.13–1.56). Conclusions: High percentage of patients had a depressive disorder with higher frequency and pain perception. So rheumatologists should be aware of this problem in order to make a proper diagnosis, optimize the application of complementary studies, and perform a multidisciplinary approach to the patient. References: Sylvia Arias, Victoria Fonsalía, Nicolás Asteggiante, Verόnica Bartesaghi. Enfermedades autoinmunitarias sistémicas y trastornos depresivos. Reumatología Clínica, Volume 7, Issue 6, Pages 389–391. Artiles-Péreza R, Lόpez-Chamόnb S. Síntomas somáticos de la depresiόn. SEMERGEN. 2009;35 supl 1:39–42. Lόpez Chamόn S. Manifestaciones clínicas de la depresiόn. Sintomatología: síntomas afectivos, de ansiedad, somáticos, cognitivos y conductuales. SEMERGEN. 2006; 32 Supl. 2:11–5. Disclosure of Interest: None declared